Audit Fee on Audit Quality in Indonesia: A Meta-Analysis Study - Rezky Alyani, Putri Dinda (Jurnal Indonesia Sosial Sains, 2023)
Various kinds of research on audit quality have been conducted and audit fees are one of the factors that affect the high and low quality of audits. In this correlation method meta-analysis study research aims to examine the relationship between audit fees and audit quality. In this study, the author conducted a review involving 37 study journals related to audit fees and audit quality in the last 5 years that have been filtered with certain eligibility criteria. The results of this study showed a correlation of 0.259 which was included in the low category and z value = 5.581; p < .001 ; 95% CI [0.168; 0.350] which means that there is a significant positive correlation between audit fees and overall audit quality from the 37 studies in the meta-analysis. So that the relationship between audit fees and audit quality is significant positive but is in the low category. These results indicate that audit fees are less directly correlated with audit quality because they have a small effect size. This indicates that there are other variables that have a greater correlation value than the audit fee. And the results of the publication bias test stated that there was no publication bias problem in the meta-analysis study.